2023
DOI: 10.3390/ijms24031893
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium-Induced Proteinuria: Mechanistic Insights from Dose–Effect Analyses

Abstract: Cadmium (Cd) is a toxic metal that accumulates in kidneys, especially in the proximal tubular epithelial cells, where virtually all proteins in the glomerular ultrafiltrate are reabsorbed. Here, we analyzed archived data on the estimated glomerular filtration rate (eGFR) and excretion rates of Cd (ECd), total protein (EProt), albumin (Ealb), β2-microglobulin (Eβ2M), and α1-microglobulin (Eα1M), which were recorded for residents of a Cd contamination area and a low-exposure control area of Thailand. Excretion o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 50 publications
(89 reference statements)
2
5
0
Order By: Relevance
“…Cd has been shown to impair the ability of the kidney to conduct proper glomerular filtration (evaluated according to the eGFR) at concentrations in the blood of 0.18 µg/L or higher, and the risk of a reduced eGFR correlates positively with the blood Cd concentration [66,84]. A similar relationship has been shown in other studies [124,164,165,167]. Ferraro et al [167] reported that the OR of a reduced eGFR reached 1.48 at a Cd concentration > 1 µg/L in the blood and urine.…”
Section: Risk Of Kidney Damage Among the General Population At Curren...supporting
confidence: 70%
See 1 more Smart Citation
“…Cd has been shown to impair the ability of the kidney to conduct proper glomerular filtration (evaluated according to the eGFR) at concentrations in the blood of 0.18 µg/L or higher, and the risk of a reduced eGFR correlates positively with the blood Cd concentration [66,84]. A similar relationship has been shown in other studies [124,164,165,167]. Ferraro et al [167] reported that the OR of a reduced eGFR reached 1.48 at a Cd concentration > 1 µg/L in the blood and urine.…”
Section: Risk Of Kidney Damage Among the General Population At Curren...supporting
confidence: 70%
“…When assessing the impact of Cd on the function of the renal glomeruli, albuminuria and parameters describing glomerular filtration, such as the GFR and eGFR, are commonly evaluated [30,37,84,164,165]. Albuminuria is the occurrence of an increased amount of albumin in the urine, presenting an albumin concentration (mg/g urine) to creatinine concentration (mg/g urine) ratio over 30.…”
Section: Biomarkers Of Cd-induced Kidney Damagementioning
confidence: 99%
“…Similar observations were then made in studies from Sweden [8,9], Australia [10], the U.S. [11], and Korea [12]. The defective tubular reabsorption of proteins, indicated by an increase in the excretion of proteins of low molecular weight, such as β 2 -microglobulin (β 2 M), is the most frequently reported sign of Cd nephrotoxicity [13,14]. In early studies, the effect of Cd on the glomerular filtration rate (GFR) involved workplace exposure, where workers were exposed mainly through the inhalation of relatively high levels of Cd in fumes and dust [15,16].…”
Section: Introductionsupporting
confidence: 56%
“…To show the effects of normalisation methods on dose-effect relationship evaluation, data on urinary excretion of Cd and various proteins recorded for residents of a Cdcontaminated area of Thailand [47] are recapitulated (Table 2). 2).…”
Section: Demonstrable Dose-response Relationshipsmentioning
confidence: 99%
“…E x , excretion of x; cr, creatinine; C cr , creatinine clearance; Cd, cadmium; β 2 M, β 2 -microglobulin; α1M, α1microglobulin; alb, albumin; Prot, protein. Numbers are the arithmetic means ± standard deviation (SD)[47]. eGFR was based on the CKD-Epidemiology Collaboration equations[48].…”
mentioning
confidence: 99%